2023
DOI: 10.5194/egusphere-2023-153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meteorological modeling sensitivity to parameterizations and satellite-derived surface datasets during the 2017 Lake Michigan Ozone Study

Abstract: Abstract. High-resolution simulations were performed to assess the impact of different parameterization schemes, surface initialization datasets, and analysis nudging on lower-tropospheric conditions near Lake Michigan. Simulations were run where climatological or coarse-resolution surface initialization datasets were replaced by high-resolution, real-time datasets depicting lake surface temperatures (SST), green vegetation fraction (GVF), and soil moisture and temperature (SOIL). Comparison of a baseline simu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…This optimized configuration is hereafter referred to as the YNT_SSNG. Otkin et al (2023) found that the AP-XM configuration generally produced more accurate meteorological analyses on the 12 km domain, but its accuracy decreased with a finer model grid resolution. In contrast, the YNT_SSNG statistics showed consistent reductions in the root mean square error (RMSE) for 2 m temperature, 2 m water vapor mixing ratio, and 10 m wind speed relative to the AP-XM as the model resolution increased from 12 to 1.3 km.…”
Section: Methodsmentioning
confidence: 96%
See 4 more Smart Citations
“…This optimized configuration is hereafter referred to as the YNT_SSNG. Otkin et al (2023) found that the AP-XM configuration generally produced more accurate meteorological analyses on the 12 km domain, but its accuracy decreased with a finer model grid resolution. In contrast, the YNT_SSNG statistics showed consistent reductions in the root mean square error (RMSE) for 2 m temperature, 2 m water vapor mixing ratio, and 10 m wind speed relative to the AP-XM as the model resolution increased from 12 to 1.3 km.…”
Section: Methodsmentioning
confidence: 96%
“…In this work, we compare two CMAQ simulations, one with baseline meteorology and the other with meteorology from our optimized Weather Research and Forecasting (WRF) model configuration, as detailed in Part I (Otkin et al, 2023). Both sets of meteorological simulations employ a triple-nested domain configuration containing 12, 4, and 1.33333 (1.3) km resolution grids, respectively (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations